Моделі раціональності в освіті (до питання про трансформаційні процеси в освіті) - Дольська, Ольга Олексіївна (Інститут філософії НАН України, 2011)
Автор пропонує методологічний підхід до розуміння трансформаційних процесів в освіті. Пропонуються моделі раціональності в освітянській практиці, серед яких особлива увага приділяється моделі комунікативної раціональності та її інваріантам. Автор вважає, що діагностика стану освіти повинна враховувати концепцію трансформацій раціональності. Аналіз концепції підкреслює людино-творчий і соціально-перетворюючий потенціал раціональності в освіті.

An author offers methodological approach to the understanding transformation processes in education. The models of rationality in elucidative practice, among which the special attention is spared to communicative rationality and its inversions, are offered. An author considers that diagnostics of the state of education must take into account conception of transformations of rationality. The analysis of conception underlines humani-creative and socially-converting potential rationality in education.
Models of rationality in education (to question about transformation processes in education)
Keywords: педагогіка; розум; мислення; підхід методологічний; раціональність комунікативна; діагностика; philosophy of education; models of rationality; communicative rationality; nonlinear transformations; pedagogical mind; thought